Endolymphatic sac tumour - Zulkarnaen , M.; Tang, I.P; Wong, S.L (Malaysian Journal Pathology, 2012)
We present a case of a papillary tumour at the cerebellopontine angle in a 41-year-old man. He presented with left-sided facial and ear pain associated with dizziness, nystagmus and hearing loss. CT scan of the temporal bone showed a destructive tumour at the left cerebellopontine angle. Surgical excision was performed and the diagnosis of the endolymphatic sac tumour was made. Endolymphatic tumour is a low grade adenocarcinoma that originates from the endolymphatic sac. The defi nitive diagnosis requires a combination of clinical features, radiological finding and pathological correlation.